MAIN COMPONENTS OF EDUCATIONAL TECHNOLOGIES AND THEIR MUTUAL INTEGRATION (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article explores the structural framework of educational technologies, which have become an integral part of the modern education system, and addresses the issues of their effective interaction. During the research, it is analyzed that educational technologies are not merely a collection of technical tools, but a holistic system comprising elements such as hardware, software, methodological support, and human resources. The primary focus of the article is directed toward the role of integrating these components in enhancing the quality of the educational process. The author substantiates the necessity of a systemic approach in implementing educational technologies and demonstrates the transformational changes resulting from the harmonization of pedagogical mastery with digital tools. The article concludes with practical recommendations for integrating structural components to improve educational efficiency.